Triggering receptor expressed on myeloid cells (TREM) like transcript-1 (TLT-1) reveals platelet activation in preeclampsia. (17th November 2022) - He, Linyan; Zhang, Yawen; Hou, Chunqi; Zhu, Ziling; He, Qi; Huang, Qin; Ji, Shundong
Abstract: Triggering receptor expressed on myeloid cells (TREM) like transcript-1 (TLT-1) is a membrane protein receptor found in α-granules of megakaryocytes and platelets. Upon platelet activation TLT-1 is rapidly relocated to the surface of platelets. In plasma, a soluble form of TLT-1 (sTLT-1) is present. Plasma levels of sTLT-1 are significantly elevated in thrombotic diseases. In the present study, we investigated to whether TLT-1 reflects platelet activation in pregnant women with preeclampsia. We studied 30 preeclamptic patients who were matched with 30 normotensive pregnant women and 30 non-pregnant controls. Basal TLT-1, P-selectin, and CD63 expressions on platelets were analyzed with the use of flow-cytometry (FCM). Platelet reactivity was induced by thrombin receptor activation peptide and determined by FCM. Plasma concentrations of sTLT-1 and soluble P-selectin (sP-selectin) were measured by an enzyme-linked immunosorbent assay. Results show that basal platelet expression of TLT-1, P-selectin and CD63 were increased in women with preeclampsia (PE) compared with normotensive pregnant women (NP). Platelets from PE women and NP women were more responsive compared to from nonpregnant women controls (NC), and which was demonstrated by increased expression of TLT-1, P-selectin, and CD63 upon stimulation in vitro . Plasma concentration of sTLT-1 was greater in PE women compared to NP women and NC women. Plasma sP-selectin level was higher in pregnant women than in nonpregnant women, but there were no significant differences between PE and NP women. In summary, our results revealed that platelet activation is prominent in preeclampsia, TLT-1 reflects platelet activation and may be a useful indicator for preeclampsia.